ЭКЗЕРСИС - ОСНОВА ФОРМИРОВАНИЯ ТЕХНИЧЕСКИХ НАВЫКОВ КЛАССИЧЕСКОГО ТАНЦА У СТУДЕНТОВ-ХОРЕОГРАФОВ - USM ADMIN (Moldova State University, 2008)
This article is dedicated to the problem of differences between classic ballet school and other choreographic direc- tions, based on a personal experience and educational activity, the knowledge of educational process of formation of the ballet artist since the first year of study and till the last year, and the development of the dancer on a professional stage. In this article it is spoken about the exercise like the basis of the whole system of the classical dance, and especially about allegro.